Anesthetic management of lung transplantation: Results from a multicenter, cross‐sectional survey by the society for advancement of transplant anesthesia. Issue 8 (24th June 2020) - Subramaniam, Kathirvel; Rio, J. Mauricio Del; Wilkey, Barbara J.; Kumar, Akshay; Tawil, Justin N.; Subramani, Sudhakar; Tani, Makiko; Sanchez, Pablo G.; Mandell, M. Susan
Abstract: Background: Current protocols for the perioperative care of lung transplant (LTX) recipients lack rigorous evidence and are often empiric, based upon institutional preferences. We surveyed LTX anesthesiologists to determine the most common practices. Methods: We developed a survey of 40 questions regarding perioperative care of LTX recipients using Qualtrics software. The survey was sent out to members of the Society of Cardiovascular Anesthesiologists performing LTX at geographically diverse sites to facilitate data collection for as many practices as possible. Results: The responses were center‐weighed (127 responses, 85% from academic settings). The clamshell approach was commonly used (70%). Cardiopulmonary bypass was preferred by 56%, ex vivo lung perfusion utilized by 43%, and 49.4% indicated they use lungs from donation after circulatory determination of death. Most (69%) used oximetric pulmonary artery catheters, 60% used tissue oximetry, and 89.3% utilized transesophageal echocardiography. Inhaled nitric oxide was preferred by 48%, restrictive fluid management by 48%, and systemic analgesia advocated by 49% of participants. Inspired oxygen concentration <30% was applied to the new lung on reperfusion by 28% of the respondents. Conclusion: Variations in healthcare delivery and utilization for LTX recipients indicate gaps in knowledge and potential opportunities to improve the quality of care.